2011
DOI: 10.1007/s12519-011-0264-x
|View full text |Cite
|
Sign up to set email alerts
|

Airway remodeling: a potential therapeutic target in asthma

Abstract: Airway remodeling may provide a possible new therapeutic target in the management of asthma. It is imperative to strengthen the research in developing new medications specifically for asthma airway remodeling. Prevention and treatment of airway remodeling become top priority in future asthma research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…It has been reported that more than 300 million people worldwide suffer from asthma and this figure is predicted to increase by another 100 million by 2025 (3). A study highlighted that the prevalence of asthma increased remarkably in the past two decades, especially in children (4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that more than 300 million people worldwide suffer from asthma and this figure is predicted to increase by another 100 million by 2025 (3). A study highlighted that the prevalence of asthma increased remarkably in the past two decades, especially in children (4).…”
Section: Introductionmentioning
confidence: 99%
“…The primary therapeutic option for asthma is to address the imbalance between Th1 and Th2 cytokines such as interleukin (IL)-4, IL-5, and IL-13 [2,3]. Although the severity of this disease is definitively dependent on the extent of airway remodeling [4], including subepithelial fibrosis, mucous hypersecretion, extracellular matrix (ECM) deposition, increased airway smooth muscle (ASM) mass, and vascular alterations [5,6], little attention has been paid to anti-remodeling as a cure for asthma. Glucocorticoids are the first-line agents for asthma patients, owning to their therapeutic effects against airway inflammation and remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been considerable progress in our understanding of the pathophysiology of asthma, the prevention and treatment of airway remodelling still constitute a significant problem. To date, long‐term medication in asthma treatment mainly focuses on anti‐inflammatory effects and there are no therapeutic interventions that can reverse established remodelling of the airways (Zhang and Li, ). AVE 0991 (AVE) is a synthetic compound that is a mimic of Ang‐(1–7) and is considered an agonist at Mas receptors (Wiemer et al ., ; Santos and Ferreira, ).…”
Section: Introductionmentioning
confidence: 99%